Weaving Cultural Threads: Integrating Local Wisdom into Indonesia’s Early Childhood Curriculum for Character Building and Cultural Preservation - Suryaningsih, Ni Made Ayu; Poerwati, Christiani Endah; Cahaya, I Made Elia (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
In an era of globalization, there is growing international interest in integrating indigenous knowledge and local wisdom into early childhood education (ECE) to promote cultural sustainability and holistic child development. However, a comprehensive synthesis of the strategies, impacts, and challenges of such integration within the Indonesian context remains limited. This article examines the incorporation of local wisdom into Indonesia’s Early Childhood Education (PAUD) curriculum as a response to cultural erosion and character development challenges. Using a descriptive qualitative approach and thematic analysis of published sources from 2019 to 2024, our analysis reveals key patterns in policy alignment, pedagogical practices, and mechanisms of cultural transmission. Grounded in socio-cultural constructivist theory and national education policy (Permendikbud No. 5 of 2022), the findings demonstrate that local wisdom-based curricula support the formation of children’s cultural identity while mitigating the homogenizing effects of globalization. Empirical illustrations include the implementation of the Tri Hita Karana philosophy in Balinese PAUD settings and culturally responsive teaching practices incorporating folklore, traditional games, and daily routines. The study also identifies the emerging potential of digital technologies, such as augmented reality (AR), to enhance children’s engagement with and retention of local wisdom values. This research contributes a conceptual model and practical recommendations for developing culturally sustainable ECE curricula, offering insights applicable to other culturally diverse, post-colonial contexts.